Research on the Civic Policy Model and Reform Innovation of Intelligent Sensor Technology Course - He, Zheng Wan (Journal of sensors, 2022)
Intelligent sensor technology is a professional course of communication, electronics, information, computer, and other related majors and is a course of expansion and extension of computer network (Ministry of Education of the People’s Republic of China, 2001). It is connected with the Internet by using information sensing device to realize the intercommunication of time and space, people, machines, and things. Intelligent sensor technology is an advanced subject; it contains a lot of ideological elements; in teaching, it should be according to the characteristics of the subject, set the goal of ideological education, to design the content of the ideological education, improve the ideological education, to carry on the course of the construction of the ideological practice and exploration, and guide students to set up the correct world outlook, the outlook on life, and values (The State Council of the Central Committee of the Communist Party of China, 2010). Integrating the elements of thinking and politics into the teaching of intelligent sensor technology and organically combining thinking and politics teaching with professional teaching is conducive to realizing the nurturing function of professional teaching and establishing an all-round curriculum system, so that professional and thinking and politics courses can go hand in hand and produce synergy. With the concept of “civic education as the soul, general education as the root, professional education as the foundation,” the strategy of integrating civic education from “point to surface (Wei, 2015), from history to the present, from inside to outside” is summarized, and a system of assessment, evaluation, and continuous improvement is established. It also establishes a system of assessment, evaluation, and continuous improvement. The strategy has proved to be effective in combining ideological and political education with moral education, enabling students to develop theoretical, institutional, and cultural confidence on the road to socialism with Chinese characteristics (Ministry of Education of the People’s Republic of China, 2004).